Urgensi Intensifikasi Program Literasi Berbasis Mata Pelajaran Bahasa Indonesia di SMP N 1 Paninggaran - Djennar Al Mayzuni; Vika Aulia Safitri; Klaudia Siti Nur Azizah; Fatma Fauziyah; M. Fauzan Amanulloh; Rissa Shofiani (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
Literacy is an important foundation in education because it plays a role in improving the ability to understand information, think critically, and support learning success. However, students' reading interest at SMP Negeri 1 Paninggaran remains relatively low, mainly due to limited access to reading materials influenced by the school's geographical condition in a mountainous area. This study aims to describe the condition of students' literacy culture, the influence of geographical conditions on literacy, the role of the Indonesian language subject in strengthening literacy, and strategies for intensifying literacy programs at school. The study employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The research informants consisted of Indonesian language teachers, library staff, and students of SMP Negeri 1 Paninggaran. The results show that students' reading interest is still low, literacy activities have not yet become a sustainable habit, and literacy-supporting facilities remain limited. Geographical conditions also affect access to reading materials and the development of students' literacy culture. The Indonesian language subject has a strategic role in strengthening literacy through the integration of reading and writing activities into the learning process. The intensification of literacy programs is carried out through the addition of Indonesian language instructional hours, optimization of the library, development of reading corners, and integration of literacy activities into classroom learning. These findings indicate that literacy strengthening based on the Indonesian language subject can be an effective strategy for building a sustainable literacy culture in the school environment.